Palmoplantar pustulosis and acrodermatitis continua of Hallopeau: demographic and clinical comparative study in a large multicentre cohort. (12th April 2022) - Assan, F.; Husson, B.; Hegazy, S.; Seneschal, J.; Aubin, F.; Mahé, E.; Jullien, D.; Sbidian, E.; D'Incan, M.; Conrad, C.; Brenaut, E.; Girard, C.; et al.
Abstract: Background: Acral pustular disease within the pustular psoriasis/psoriasis‐like spectrum mainly includes palmoplantar pustulosis (PPP) and acrodermatitis continua of Hallopeau (ACH). Scarce data argue for a distinction between these two entities, but no study has compared the clinical and epidemiologic characteristics of ACH and PPP. Objectives: We aimed to perform a comparative description of the epidemiological and clinical characteristics of PPP and ACH in a multicentre retrospective cohort. Methods: In this multicentre national retrospective cohort study, we compared the epidemiological characteristics, comorbidities and psoriasis characteristics of patients with PPP and ACH. Results: A total of 234 patients were included: 203 (87%) with PPP, 18 (8%) with ACH and 13 (6%) with both, according to 2017 ERASPEN criteria. As compared with ACH, PPP was associated with female sex, smoking activity and higher median BMI ( P = 0.01, P = 0.02 and P = 0.05 respectively). A family background of psoriasis was more frequent in PPP than ACH. Age of onset of palmoplantar disease was similar between PPP and ACH patients, median age 44 and 48 years respectively. Peripheral joint inflammatory involvement was the only rheumatic disease associated with ACH. The association with another psoriasis type was similar in PPP and ACH (57.6% and 61.1% respectively). Conclusion: Our study confirms in a large PPP cohort the predominance of females and a high prevalence of smoking and elevated body mass index but also shows an association of these features in PPP as compared with ACH. In addition, it highlights peripheral arthritis as the only arthritis endotype associated with ACH. Increased knowledge of the immunogenetic backgrounds underlying these two entities is warranted to better stratify pustular psoriasis or psoriasis‐like entities for precision medicine.